Infectious disease among enslaved African Americans at Eaton's Estate, Warren County, North Carolina, ca. 1830-1850 - Patricia M Lambert (Memorias do Instituto Oswaldo Cruz, 2006)
The skeletal remains of 17 people buried in the Eaton Ferry Cemetery in northern North Carolina provide a means of examining health and infectious disease experience in the XIX century South. The cemetery appears to contain the remains of African Americans enslaved on the Eaton family estate from approximately 1830-1850, and thus offers a window into the biological impacts of North American slavery in the years preceding the Civil War. The sample includes the remains of six infants, one child, and one young and nine mature adults (five men, four women, and one unknown). Skeletal indices used to characterize health and disease in the Eaton Ferry sample include dental caries, antemortem tooth loss, enamel hypoplasia, porotic hyperostosis, periosteal lesions, lytic lesions, and stature. These indicators reveal a cumulative picture of compromised health, including high rates of dental disease, childhood growth disruption, and infectious disease. Specific diseases identified in the sample include tuberculosis and congenital syphilis. Findings support previous research on the health impacts of slavery, which has shown that infants and children were the most negatively impacted segment of the enslaved African American population.